1993
DOI: 10.1111/j.1365-2222.1993.tb00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of basophils by immunohistochemistry in the airways of post‐mortem cases of fatal asthma

Abstract: There is increasing evidence for the role of basophils in the pathogenesis of bronchial asthma. To examine the presence of basophils in the airways of patients with fatal asthma by immunohistochemistry, we stained lung tissues from four post-mortem cases who had died from severe asthmatic attacks and four controls with a monoclonal antibody raised against tryptase (AA-1) and anti-IgE. Mast cells and basophils were identified in the bronchioles as AA-1- and anti-IgE-positive cells, and anti-IgE-positive cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 31 publications
2
56
0
1
Order By: Relevance
“…In asthma and, according to some reports, in nonasthmatic subjects, the ASM bundle is infiltrated by mast cells, predominately of the chymase-positive phenotype [11][12][13][14][15][16][17][18]. Mast cell-ASM interactions in asthma are summarised in figure 1.…”
Section: Inflammatory Cell Localisation To Asm Bundlementioning
confidence: 99%
See 1 more Smart Citation
“…In asthma and, according to some reports, in nonasthmatic subjects, the ASM bundle is infiltrated by mast cells, predominately of the chymase-positive phenotype [11][12][13][14][15][16][17][18]. Mast cell-ASM interactions in asthma are summarised in figure 1.…”
Section: Inflammatory Cell Localisation To Asm Bundlementioning
confidence: 99%
“…To date, little attention has been paid to the localisation of inflammatory cells within structural compartments of the airway wall. Recently, enthusiasm for the view that microlocalisation is important in obstructive airway diseases has been fuelled by studies showing inflammatory cells within the ASM in asthma [11][12][13][14][15][16][17][18] and COPD [19], but not in normal controls. Most notably, in asthma the ASM is infiltrated by mast cells and the number of mast cells within the ASM bundle was associated with the degree of AHR [11].…”
mentioning
confidence: 99%
“…5 Basophils are found in the lungs of patients with allergic asthma, and probably contribute to pathogenesis during fatal asthma. 6,7 On the other hand, they might contribute to protective immunity against helminths since basophils are an important source for IL-4 and IL-13. 8 Recently, basophils have been shown to be implicated in polarization of T-helper 2 (Th2) cells by allergens with protease activity 9 and IgG1-mediated anaphylaxis, 10 which further demonstrates their important functions during type 2 immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-four hours after ICHT-F in Group A, the level of IL-18 correlated with the proportion of basophils at the 4 h time-point. These cells are major inducers of allergic infl ammation [18][19][20]. Yoshimoto et al [31] has demonstrated that IL-18 has a potential to stimulate basophils to release large amounts of IL-4 and IL-13 in vitro in the presence of IL-3.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-four hours after the provocation with fl our allergens, basophil proportion was also signifi cantly higher in Group A than in Group C. Basophils play a signifi cant role in allergic response [17]. They have been reported in the respiratory tract of patients dying of asthma, during the exacerbations of this disease and during the late asthmatic response to the allergen [18][19][20]. It is estimated that in the late asthmatic reaction, more than 95% of all metachromatic cells in the bronchoalveolar lavage fl uid are basophils [20,21].…”
Section: Il-18 Levels In Nlf After Icht-fmentioning
confidence: 99%